2018
DOI: 10.1177/2327857918071045
|View full text |Cite
|
Sign up to set email alerts
|

How Nurses Identify Hospitalized Patients on Their Personal Notes: Findings From Analyzing ‘Brains’ Headers with Multiple Raters

Abstract: The overarching objective of this research is to reduce the burden of documentation in electronic health records by registered nurses in hospitals. Registered nurses have consistently reported that e-documentation is a concern with the introduction of electronic health records. As a result, many nurses use handwritten notes in order to avoid using electronic health records to access information about patients. At the top of these notes are patient identifiers. By identifying aspects of good and suboptimal head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The interrater agreement was confirmed to be acceptable (Cohen’s kappa = 0.94) using the codebook for content categories on the “brain.” We divided the analysis into content included in the “header” and “body” of the “brain.” All of the “brains” included a header which was unique to the patient (see Sarkhel et al, 2018, for the characteristics of a good and bad header design based on multiple raters analyzing the “brain” headers). The header is defined as the information displayed in an area at the top of the page, visually separated with white space or a line from the remaining body content, which included patient identifier information and other patient information deemed of high importance by the nurse.…”
Section: Resultsmentioning
confidence: 99%
“…The interrater agreement was confirmed to be acceptable (Cohen’s kappa = 0.94) using the codebook for content categories on the “brain.” We divided the analysis into content included in the “header” and “body” of the “brain.” All of the “brains” included a header which was unique to the patient (see Sarkhel et al, 2018, for the characteristics of a good and bad header design based on multiple raters analyzing the “brain” headers). The header is defined as the information displayed in an area at the top of the page, visually separated with white space or a line from the remaining body content, which included patient identifier information and other patient information deemed of high importance by the nurse.…”
Section: Resultsmentioning
confidence: 99%
“…Although using room numbers is an unacceptable method for identifying a patient (WHO, 2007), they were frequently handwritten on handover tools. Sarkhel et al (2018) found hospital nurses primarily use room numbers as patient identifiers due to geographic location serving as a static memory aid. Nurses often are assigned a group of rooms on a given shift regardless of patient turnover due to admissions and discharges.…”
Section: Discussionmentioning
confidence: 99%
“…how the summaries came to be, the answer still remains illusive. Explaining how a machine-generated summary was constructed, has become a necessity under the newly introduced General Data Privacy Regulation Act (ITGP, 2017), especially for applications in enterprise (Sarkhel and Nandi, 2019;Keymanesh et al, 2020) and biomedical domain (Moradi and Ghadiri, 2018;Sarkhel et al, 2018). Some recent efforts have proposed using interpretable heatmaps (Baan et al, 2019) generated from the attention distribution over an input sequence for interpreting model behaviour.…”
Section: Prototype Summarymentioning
confidence: 99%